Fast-ion velocity-space tomography using slowing-down regularization in EAST plasmas with co- and counter-current neutral beam injection. (5th October 2020) - Madsen, B; Huang, J; Salewski, M; Järleblad, H; Hansen, P C; Stagner, L; Su, J; Chang, J F; Fu, J; Wang, J F; Liang, L Z; Zhong, G Q; et al.
Abstract: We demonstrate 2D reconstructions of the fast-ion velocity distribution from two-view fast-ion D-alpha (FIDA) measurements at the EAST tokamak. By expressing the distribution in a basis relying on the fast-ion slowing-down process in fusion plasmas, the smoothness and velocity-space resolution of reconstructions are improved. We reconstruct distributions of fast ions born from simultaneous co- and counter-current neutral beam injection and detect the expected distinct change in fast-ion birth pitch when comparing discharges utilizing different neutral beam injectors. For purely co-current injection, we find a good agreement between TRANSP-predicted and reconstructed fast-ion densities, pressures and current densities for energies above 20 keV. We furthermore illustrate the improvement of the reconstructed high-energy range (> 40 keV) of the distribution by combining FIDA with neutron emission spectroscopy measurements with the compact single-plate EJ301 scintillator.